Habits Die Hard: The Semiotics of Wolf Management in Finland - Hiedanpää, Juha (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2021)
Finland has struggled to formulate and implement policies for the national grey wolf (Canis lupus) population. Institutional adjustments were undertaken to improve wolf protection and human–wolf coexistence, but the wolf population has decreased. This calls for an explanation. I will apply Charles S. Peirce’s concept of habits and his semiotic theory to understand why it so difficult to design and implement a workable wolf policy. I intertwine Peircean methodology with the ontology provided by ecological economics and the analytic epistemic tools by old (traditional) institutional economics. Institutions exist to serve human purposes, and the modification of institutional infrastructure affects how social-ecological functions can still bring absent features of policy and management into existence. I therefore explicate the semiotic interplay of policy signs, objects, and interpretants in wolf management adjustments and consequent outcomes. Finally, the difficulty of habit formation for coexistence will be discussed and policy advice given.